2019
DOI: 10.1002/2211-5463.12574
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant yeast VDAC2: a comparison of electrophysiological features with the native form

Abstract: Voltage‐dependent anion channel isoform 2 of the yeast Saccharomyces cerevisiae ( yVDAC 2) was believed for many years to be devoid of channel activity. Recently, we isolated yVDAC 2 and showed that it exhibits channel‐forming activity in the planar lipid bilayer system when in its so‐called native form. Here, we describe an alternative strategy for yVDAC 2 isolation, through heterologous expression in bacteria and refo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The electrophysiology at the PLB revealed that both native and recombinant proteins were able to form pores with the same, typical VDAC-like conductance of ∼3.6 nS in 1 M KCl, as displayed in Figure 2A) (Guardiani et al, 2018;Magrì et al, 2019). As for voltage-dependence, native yVDAC2 resembled yeast or human VDAC1, even if it began to close at ±40-50 mV.…”
Section: Yeast Vdac2 Has Pore Forming Activity and A Peculiar Ion Selectivitymentioning
confidence: 89%
See 3 more Smart Citations
“…The electrophysiology at the PLB revealed that both native and recombinant proteins were able to form pores with the same, typical VDAC-like conductance of ∼3.6 nS in 1 M KCl, as displayed in Figure 2A) (Guardiani et al, 2018;Magrì et al, 2019). As for voltage-dependence, native yVDAC2 resembled yeast or human VDAC1, even if it began to close at ±40-50 mV.…”
Section: Yeast Vdac2 Has Pore Forming Activity and A Peculiar Ion Selectivitymentioning
confidence: 89%
“…It was called native yVDAC2. The second strategy applied the heterologous expression of a 6xHis-tagged yVDAC2 in E. coli ( Magrì et al, 2019 ). Being a membrane protein, yVDAC2 localized in the inclusion bodies and needed high concentrations of denaturant to be purified, followed by a refolding step in presence of specific detergents ( Engelhardt et al, 2007 ).…”
Section: Yeast Vdac2 Has Pore Forming Activity and A Peculiar Ion Selectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Our group expressed the yeast VDAC2 isoform and characterized its activity after reconstitution in planar membranes. We found that recombinant yVDAC2 is also able to fold forming a pore and that its electrophysiological characteristics are very similar to those of yVDAC1 [ 83 , 84 ]. While the expression pattern and the physiological role of yVDAC2 remain unknown, knockout out of yVDAC1 forces cells to adopt a fermentative energy metabolism, highlighting the failure of yVDAC2 to compensate for the lack of yVDAC1 [ 82 ].…”
Section: The Role Of Vdac Isoforms In Yeastmentioning
confidence: 99%